DIGITAL TRANSFORMATION STRATEGY FOR IMPLEMENTING HALAL MANAGEMENT: A CASE STUDY OF THE MSME INDUSTRY IN PAKISTAN - Hermawan Adinugraha, Hendri; Rahmawati, Ferida; Shulthoni, Muhamad; Sain, Zohaib Hassan (Balai Penelitian dan Pengembangan Agama Makassar, 2025)
This research examines digital transformation strategies for implementing halal management in the MSME industry in Pakistan. The main problem in this research is the low level of adoption of digital technology in the halal MSME sector, which is caused by limited resources, low digital literacy, and a lack of regulations that support digitalization. This research analyzes strategies halal MSMEs can implement to utilize digital technology to increase business efficiency, expand market access, and ensure compliance with halal standards. This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews, participant observation, and document analysis from various sources, including MSMEs, halal certification institutions, and digital economy experts. Analysis was carried out using the Miles and Huberman model, including data reduction, presentation, and conclusion. The research results show that digital transformation can increase the competitiveness of halal MSMEs through the adoption of e-commerce, social media-based marketing, and Sharia-based digital payment systems. However, challenges in implementing technology are still significant, especially in regulation and digital literacy. Therefore, synergy is needed between the government, academia, and the private sector to create a business environment that supports the digital transformation of halal MSMEs in Pakistan.